2014
DOI: 10.5195/cajgh.2013.97
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of synovium-derived mesenchymal stem cells and hyaluronic acid promote regeneration of massive cartilage defects in rabbits

Abstract: IntroductionThe purpose of this study was to investigate whether intra-articular injection of synovium-derived mesenchymal stem cells (SD MSCs) with low molecular weight hyaluronic acid (HA) could promote regeneration of massive cartilage in rabbits.Material and methodsThe SD MSCs were harvested from the knees of 10 Flemish giant rabbits, expanded in culture, and characterized. A reproducible 4-mm cylindrical defect was created in the intercondylar groove area using a kit for the mosaic chondroplasty of femora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In the current study, we found that the combinatory use of BMSCs and HA improves the cartilaginous healing of chondral defects, both macroscopically and microscopically. The results were in line with other stem-cell-based injection studies with rat, rabbit, and canine models [ 17 , 18 , 19 ]. Interestingly, most studies consistently reported the superior efficacy of combined BMSCs and HA on chondral defect healing than that of isolated stem cells or HA alone.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current study, we found that the combinatory use of BMSCs and HA improves the cartilaginous healing of chondral defects, both macroscopically and microscopically. The results were in line with other stem-cell-based injection studies with rat, rabbit, and canine models [ 17 , 18 , 19 ]. Interestingly, most studies consistently reported the superior efficacy of combined BMSCs and HA on chondral defect healing than that of isolated stem cells or HA alone.…”
Section: Discussionsupporting
confidence: 89%
“…Unlike conventional treatment modalities, which need open surgery for cells or scaffold transplantation, direct stem cell injection emerges as a simple, minimally invasive, and attractive therapeutic approach for treating chondral defects in recent years. Moreover, many studies have reported promising results of stem-cell-based injection therapy in promoting cartilage repair and regeneration [ 12 , 13 , 17 , 18 , 20 , 29 , 30 , 31 , 33 ]. Mcllwraith et al showed that full-thickness chondral defects in an equine model treated with microfracture followed by IA BMSC injection have superior outcomes than microfracture alone [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, JW-AKT rabbits could serve as an alternative candidate for an animal model to replace dogs because of their body size and easiness in handle. The larger rabbit (including Flemish giant) models have been employed for medical research with surgical treatments especially in vascular [2, 9, 17] and orthopedic [3,4,5, 12, 13, 23] experiments. Additionally, large body size is advantageous in collection of a large amount of biological specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Larger rabbit (including Flemish giant) models have been employed for medical research, especially in those that involved surgical treatment including vascular [2, 9, 17] and orthopedic [3,4,5, 12, 13, 23] surgery due to its body size. Because of recent greater animal welfare advocacy for the ethical treatment, it is getting harder to use dogs as an experimental animal [19].…”
mentioning
confidence: 99%